DEVELOPMENT OF WAYS OF INCREASING THE RELIABILITY OF THE INTEGRATED COMPLEX OF SATELLITE AND INNERATION NAVIGATION SYSTEMS - Dmitriev, Oleg; Kushnerova, Nadiia; Profatilov, Stanislav (Proceedings of National Aviation University (archive), 2018)
Purpose: is an analysis of methods and models for ensuring the functions of controlling the integrity of the GNSS and functional diagnostics of the INS in flight conditions, as well as developing an algorithm for monitoring the integrity of the GNSS and controlling the correct functioning of it. Methods: methods of the theory of optimal estimation, the theory of probability and the theory of random processes.Results: The analysis of factors influencing the quality of autonomous monitoring of the integrity of the satellite radionavigation system and analysis of possible ways to increase reliability and integrity were carried out. An algorithm for monitoring the integrity of the GNSS and controlling the correct functioning of the INS has been developed.Discussion: Based on the results of the study it is proposed to develop mathematical complex, which allows to conduct a complete cycle of simulation of the algorithm at a given stage of flight of the aircraft using existing groupings of spacecraft, as well as experimental navigation data of the GNSS and the INS, registered during the flights.